Permanent Brachial Plexus Birth Injury: Helsinki Shoulder Protocol - Grahn, Petra; Pöyhiä, Tiina; Nietosvaara, Yrjänä (Seminars in Plastic Surgery, 2023)
Passive shoulder exercises from birth and ultrasound screening from 3 to 12 months. Botox is given to shoulder internal rotators and a bracing commenced, if alpha-angle exceeds 30°, or passive shoulder external rotation is below 70 degrees. Plexus reconstruction is recommended to children with root avulsion(s) on magnetic resonance imaging or 3-month Toronto Test Score < 3.5. Specific neurotization is recommended to children without avulsions, but lack of progress in healing. Shoulder dysplasia was diagnosed in 49% of 270 patients with permanent brachial plexus birth injury in our catchment area from 1995 to 2021. The age at detection of shoulder dysplasia dropped from mean 5.4 years in children born before 2000 to mean 3.9 months in children born after 2009. Botox was given to 57% of the patients born after 2009. Rate of shoulder relocation decreased from 28 to 7% while mean active shoulder external rotation in adduction increased from 2 to 46°.
Keywords: brachial plexus birth injury; infraspinatus; neurotization; botox; shoulder contracture; shoulder; subluxation; ultrasound; screening; glenohumeral joint; dysplasia; external rotation